Mekanisme Good Corporate Governance (GCG) terhadap manajemen laba - Ramdhanti, Moza; Indrati, Menik (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of good corporate governance mechanisms as measured by the Independent Board of Commissioners, Audit Committee, Auditor Quality, and Institutional Ownership on Earnings Management. The population in this study are manufacturing companies in the food and beverage sector which are listed on the Indonesia Stock Exchange (IDX) in 2018-2021. This study uses multiple linear regression analysis method, and uses the application of the Statistical Program for Social Science (SPSS). The population in this study were 26 food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period and the sample used was 20 companies using a purposive sampling technique. The results of this study indicate that the Independent Board of Commissioners variable has a negative effect on Earnings Management. The Audit Committee variable has a negative effect on Earnings Management. Auditor Quality variable has a negative effect on Earnings Management. Institutional Ownership Variables have a negative effect on Earnings Management. This research for the company is expected by the management to be more careful in including costs or expenses in the calculation of profit. If an error occurs, the earnings management carried out will have an impact. Meanwhile, prospective investors should be more careful in making investment decisions in companies that are carried out by assessing the quality of earnings in the observation period presented in the financial statements.